Performance assessment of HC-290 as a drop-in substitute to HCFC-22 in a window air conditioner - Devotta, S; Padalkar, AS; Sane, NK (International Journal of Refrigeration - Revue Internationale Du Froid, 2005)
As per the Montreal Protocol, CFCs and HCFCs are being phased out. HCFC-22 is used in window air conditioners. This paper presents the experimental performance study of a window air conditioner with propane (HC-290), a natural refrigerant, as a drop-in substitute to HCFC-22. Experimental results showed that HC-290 had 6.6% lower cooling capacity for the lower operating conditions and 9.7% lower for the higher operating conditions with respect to HCFC-22. The coefficient of performance for HC290 was 7.9% higher for the lower operating conditions and 2.8% higher for the higher operating conditions. The energy consumption of the unit with HC-290 was lower in the range 12.4-13.5% than HCFC-22. The discharge pressures for HC-290 were lower in the range 13.7-18.2% than HCFC-22. For HC-290, the pressure drop was lower than HCFC-22 in both heat exchangers. This paper also presents simulation results for the heat exchangers of an HCFC-22 window air conditioner with HC-290 as a drop-in substitute. The simulation has been carried out using EVAP-COND, a heat exchanger model developed by NIST [National Institute of Standards and Technology. EVAP-COND: simulation models for finned-tube heat exchangers, Maryland, USA (2003). http://www2.bfrl.nist.gov/software/evap-cond/ [18]]. The simulated evaporator capacities are within +/- 4% of the experimentally measured cooling capacities for both refrigerants. Simulation results for HC-290 and HCFC-22 are compared. The exit temperatures of HC-290 are lower by 0.3-1.2 degrees C in the condenser and are higher by 2.1-2.4 degrees C in the evaporator than HCFC-22. Evaporating pressures of HC-290 are lower by 2.1-3.3% as compared to HCFC-22. The pressure drops of HC-290 are lower in both the evaporator and the condenser as compared to HCFC-22. The outlet temperatures of air for HCFC-22 and HC-290 in both heat exchangers are nearly the same. (c) 2005 Elsevier Ltd and IIR. All rights reserved.
Keywords: air conditioner; COP; Evaporator; experiment; performance; propane; R-22; simulation; window